A Primer on the Role of TP53 Mutation and Targeted Therapy in Endometrial Cancer - Bohao Zhang; Haozhe Zhang; Yanru Qin (Frontiers in Bioscience-Landmark)
Endometrial Cancer (EC) is one of the most common gynecological malignancies, ranking first in developed countries and regions. The occurrence and development of EC is closely associated with genetic mutations. TP53 mutation, in particular, can lead to the dysfunction of numerous regulatory factors and alteration of the tumor microenvironment (TME). The changes in the TME subsequently promote the development of tumors and assist in immune escape by tumor cells, making it more challenging to treat EC and resulting in a poor prognosis. Therefore, it is important to understand the effects of TP53 mutation in EC and to conduct further research in relation to the targeting of TP53 mutations. This article reviews current research progress on the role of TP53 mutations in regulating the TME and in the mechanism of EC tumorigenesis, as well as progress on drugs that target TP53 mutations.